Upaya Pendidikan Agama Islam Dalam Mengatasi Distorsi Moral Siswa Akibat Media Sosial - Zahraini, Zahraini; Hajaroh, Siti (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Considering the rampant moral distortion that is happening among students today so that this phenomenon triggers unrest in many circles, especially teachers, parents and society, this causes this research to be carried out. This research aims to describe the efforts that have been made to overcome students' moral distortions through Islamic religious education. This research uses descriptive qualitative method based on literature study.  The technique for collecting data uses documentation studies in the form of library data derived from articles, journals and various relevant books.  The findings in this study indicate that there are various kinds of moral distortions that have been committed by students such as cyberbullying, spreading hoax, sexual harassment, drinking alcohol, consuming drugs, free sex, and others.  The efforts in overcoming moral distortions among students are carried out through the development of a holistic Islamic Education (PAI) curriculum, instilling student character education, taking a holistic and collaborative approach from family, school, and community.